Genotypic variation in agronomic and physiological responses of potato cultivars to water stress under greenhouse conditions - Chairi, Fadia; Lateur, Marc; MuhovskI, Yordan (Frontiers in Plant Science, 2025)
Due to the effects of climate change, conditions tend to be increasingly extreme, with water availability being one of the main limiting factors in potato production. The objective of this study was to analyze the differential response of physiological and yield components in eight potato varieties under water deficit conditions. For this purpose, a greenhouse trial was carried out with the varieties Bintje, Montis, Sevilla, Lady Jane, Louisa, Dior, Acoustic and Tentation. Varieties were submitted to a moderate water stress (MS) and severe water stress (SS) from 23 days after planting (DAP) until 55 DAP and compared to well-watered (WW) condition. Data were collected on morphological traits such as plant height and root length and weight. As well as the physiological traits such as stomatal conductance (gs), chlorophyll and Flavonoid content, relative water content (RWC), water use efficiency (WUE) and carbon isotope composition. At 55 DAP yield components were determined. Variation of all parameters (Δ) in comparison with control were calculated and contrasted with a drought tolerant index (TDI). Drought stress significantly reduced biomass, tuber number, and plant height, but genotypes responded differently, reflecting notable genetic diversity in tolerance mechanisms.